(untitled) (Journal of Contemporary Philology, 2018)
What is the ontological status of a character in narrative in the wake of the new materialist turn? This essay presents an examination of the latent humanism at work in the conception of character. I begin with the destabilization of the category of human made possible by Gilles Deleuze’s work on perturbation. I also rely on more recent calls for a nonhuman ontology of critique in the work of Lauren Berlant and Jane Bennett, and argue that an anticharacterological reading of a narrative might reveal more about why things happen to people in the neoliberal matrix of late capitalism.